Achieving customer loyalty through service excellence in internet industry. Issue 4 (11th November 2014) - Thaichon, Paramaporn; Lobo, Antonio; Mitsis, Ann
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to investigate the antecedents to attitudinal and behavioural loyalty of customers of Internet service providers (ISPs). In addition, this study endeavours to identify the relationship between overall service quality and cognitive as well as affective evaluations of customers. An assessment of service quality dimensions is also included to fill the void of research on modelling service quality in high tech services. Design/methodology/approach – The paper reviews the most cited articles on the topic published in academic journals with a view to identify dimensions that customers use to evaluate the quality of a service providers, and to determine loyalty formation through customer cognitive and affective evaluations in Internet industry. Findings – The exogenous constructs of the conceptual model include influential factors such as network quality, customer service, information support and security which make up the perception of overall service quality. The endogenous constructs include cognitive and affective determinants such as customers' trust, satisfaction, commitment, value and resultants – attitudinal loyalty and behavioural loyalty. Originality/value – The study proposes that by enhancing service quality, firms can influence customers' satisfaction, trust, commitment and value, and ultimately loyalty, which are critical for an ISP's success and long-term sustainability. Moreover, applying the findings of this study, ISPs can strategise in making customers more central in their day to day operations, which would create competitive advantage for the companies.